Asian models of entrepreneurship : from the Indian Union and Nepal to the Japanese archipelago : context, policy and practice - Dana, Leo Paul, (Asia-Pacific business series, 2014)
"In this book, Leo-Paul Dana makes it clear that much can be learnt about the nature of entrepreneurial activity when we delve into the unique characteristics of different nations of South Asia, South-east Asia and East Asia. Through in-depth analyses and comprehensive reviews of many Asian countries, the profound differences both among and within countries of the region become vividly apparent"--